Improved productivity of goats and utilisation of goat milk in Nigeria - Egwu, G.O.; Onyeyili, P.A.; Chibuzo, G.A.; Ameh, J.A. (Elsevier, 1995)
Nigeria, with an estimated total livestock production of 52.4 million, of which goats constitute about 26.5 million, still has inadequate meat and milk production. This review describes the three distinct breeds of goats (Sahel, Red Sokoto, and West African Dwarf) with their traditional husbandry systems. The use of alternative high energy feeds for goats in Nigeria is described. Common disease constraints, helminthiasis, blood borne parasites, contagious caprine pleuro-pneumonia, and peste de petit ruminants (PPR), militating against effective goat production in Nigeria are also discussed. Goat meat and milk of the common breeds in Nigeria are important. With the provision of goat breeding and multiplication centres in Nigeria and increased general awareness and consumption of goat milk, the country could strive for self-sufficiency in meat and dairy production.